Performance of a lipase-catalyzed transesterified palm kernel olein and palm stearin blend in frying banana chips - Chu, B.S; Ghazali, H.M; Lai, O.M; Che Man, Y.B; Yusof, S; Yusoff, M.S.A (2001)
The frying performance of an enzymatically transesterified palm stearin and palm kernel olein (1:1 by weight) blend was compared with its control (physical mixture or no enzyme added) and a commercial plastic frying shortening (CS). The samples were used as deep-fat frying media at 180°C for banana chips for seven consecutive days. The samples were then analysed for iodine value (IV), free fatty acid (FFA) content, peroxide value (PV), thiobarbituric acid (TBA) value, p-anisidine value (AV), total polar compounds (TPC), fatty acid composition, specific extinction, E1%1cm at 233 and 269 nm, polymer contents, viscosity and colour indices. The fried banana chips were analysed for acceptability by sensory evaluations. Storage properties of the banana chips were also evaluated by trained sensory panellists and a modified TBA test. The transesterified blend was found to have significantly (P<0.05) higher IV, FFA, PV, TBA value, AV, TPC, E1%1cm at 233 and 269 nm values, polymer content, viscosity and colour indices compared to the control, indicating that the transesterified blend was more susceptible to oxidative deterioration during deep-fat frying. CS generally showed the largest changes in most of the parameters, basically due to its high polyunsaturated fatty acid levels. There was no significant difference (P>0.05; for all the attributes tested) between the acceptability of the banana chips fried by the transesterified and control blends. However, the banana chips fried in CS had significantly (P<0.05) lower scores in terms of flavour, aftertaste and overall acceptability. This might be due to the typical hydrogenation flavour of CS. In the storage stability study of the banana chips, it was found that the banana chips fried in the transesterified blend were significantly (P<0.05) more rancid (lower score in sensory evaluations) and had a higher TBA value at the end of the storage time than the control. Copyright © 2001 Elsevier Science Ltd.